The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00384-020-03530-0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of tined lead migration in sacral nerve modulation

Abstract: Aim Lead migration is a common cause of loss of efficacy in sacral nerve modulation. Our aim was to systematically study the migration pattern of tined leads in sacral nerve modulation. Our hypothesis was that tined leads may promote forward migration because of their configuration. Method Consecutive patients treated with sacral nerve modulation with a tined lead electrode, who had experienced loss of efficacy and had radiographs both at baseline and after loss of efficacy between 2005 and 2016 were eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For the diagnosis of migration posterior-anterior and lateral radiographs at baseline and after the loss of efficacy are fundamental. Small changes in the lead position are very common, Ezra E et al, reported some degree of lead migration in 100% of their patients, 35% migrated backward and 74% of the patients had a forward migration [8]. A forward migration was observed in 50% of the patients who suffered loss of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For the diagnosis of migration posterior-anterior and lateral radiographs at baseline and after the loss of efficacy are fundamental. Small changes in the lead position are very common, Ezra E et al, reported some degree of lead migration in 100% of their patients, 35% migrated backward and 74% of the patients had a forward migration [8]. A forward migration was observed in 50% of the patients who suffered loss of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing SNM trial success in patients with overactive bladder, urinary retention and FI found no continuous association between the motor thresholds and trial success ( Adelstein et al, 2019 ). Further, lead migration post-implantation is a common occurrence which requires reprogramming and can lead to loss of efficacy ( Ezra et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%